A case of Aspergillus and Nocardia infections after bronchial thermoplasty. Issue 2 (28th November 2018) - Matsubayashi, Sachi; Iikura, Motoyasu; Numata, Takanori; Izumi, Shinyu; Sugiyama, Haruhito
Abstract : Bronchial thermoplasty (BT) is a bronchoscopic treatment for severe asthma. A 35‐year‐old woman with uncontrolled severe asthma despite maximal pharmacological treatment underwent BT and started coughing after the first procedure. One month later, during the second BT procedure, there were white ulcerous lesions on the right B9 bronchus. Culture of the bronchial brushing specimen showed Aspergillus fumigatus, for which voriconazole was started for treatment. On the third BT procedure, endobronchial mucus sampling demonstrated Nocardia spp., for which trimethoprim‐sulfamethoxazole was given for three months. Seven months after the third BT procedure, no particular endobronchial lesions were found, and no abnormal pathogens were obtained by culture. The resulting bronchial infection in this case may be attributed to the use of systemic steroids, which rendered the patient immunocompromised, and to tissue fragility that was caused by the thermal energy from the BT procedure. Culture of endobronchial mucus should be considered during BT. Abstract : Bronchial thermoplasty (BT) is a bronchoscopic procedure that uses thermal energy to reduce airway smooth muscle mass for treating uncontrolled severe asthma. Bronchial oedema and radiologic changes are generally known as the major complications of BT, but infections have rarely been reported. We describe a case of fungal and bacterial infections that developed after BT.